SLM Printed Waveguide Dual-Mode Filters With Reduced Sensitivity to Fabrication Imperfections - Wen, Xiaozhu; Guo, Cheng; Shang, Xiaobang; Yu, Yang; Shu, Minjie; Yang, Qian; Li, Sheng; Attallah, Moataz M.; Liu, Hongzhong; Zhang, Anxue (IEEE microwave and wireless components letters, 2021)
This letter presents an eighth-order dual-mode waveguide filter, fabricated using the selective laser melting (SLM) technique. The filter employs four dimpled ellipsoid dual-mode resonators, operating at the fundamental TM 101 mode. During printing, the filter can be mechanically self-supported without any internal supports. Compared to the filters employing tuning posts, the proposed filter is less sensitive to fabrication errors in terms of their impacts on passband return loss (RL), frequency shift, and bandwidth. The filter was demonstrated at WR-112 band (7-10 GHz), with a measured insertion loss of 0.25-0.4 dB and an RL >15 dB across the passband of 8-8.46 GHz.